2015
DOI: 10.1097/jto.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study on Early Detection of Lung Cancer with MSCT in Germany: Results of the First 3 Years of Follow-up After Randomization

Abstract: Introduction:The German Lung Cancer Screening Intervention Trial (LUSI) is one of the European randomized trials investigating the efficacy of low-dose multislice computed tomography (MSCT) as a screening tool for lung cancer. In the evaluation of the first (prevalence) screening round, we observed exceptionally high early recall rates, which made the routine application of MSCT screening questionable. Because screening may behave differently in subsequent (incidence) screening rounds, we analyzed (a) basic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
63
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 14 publications
(9 reference statements)
5
63
1
13
Order By: Relevance
“…The higher recall rate at T0 in both LDCT arms was also observed by other European studies and NLST [15,17,18]. However, the recall rates across the screening rounds of MILD (1-15 % in LDCT1 and 3.1-14 % in LDCT2) were lower than those reported by the other studies (3.8-27.9 %) [15,17,18].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…The higher recall rate at T0 in both LDCT arms was also observed by other European studies and NLST [15,17,18]. However, the recall rates across the screening rounds of MILD (1-15 % in LDCT1 and 3.1-14 % in LDCT2) were lower than those reported by the other studies (3.8-27.9 %) [15,17,18].…”
Section: Discussionsupporting
confidence: 44%
“…However, the initial detection rate in LDCT2 (0.52) was lower than those reported by other trials (0.8-2.2 %), and increased among participants shifted into the LDCT2 arm with annual follow-up, as compared to those who remained in the arm with biennial follow-up. [17,18]. This finding suggests that a tighter follow-up would be more appropriate for participants with indeterminate or positive findings, despite negative initial diagnostic workup.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…At least one subject with MPLC was reported in 11/33 studies (5,13-18,24-35), with a mean cumulative frequency of 0.18% (136 subjects) in 71,901 screenees and of 11.6% in 1,170 subjects with at least one screen-detected lung cancer (19)(20)(21)(22)(23)(36)(37)(38)(39)(40)(41)(42)(43)(44). The MPLC were considered synchronous in 123/136 (90%) subjects and metachronous in 13 (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Three low-quality trials compared annual screening with low-dose CT to no screening or usual care and found no difference in lung cancer-specific mortality (RR 1.30, 95% CI 0.81-2.11) or all-cause mortality (RR 1.38, 95% CI 0.86-2.22) after five years or less of followup. 12 A recent update of the literature search found one randomized study 15 presenting interim results on early detection of lung cancer with low-dose multislice CT (compared with no screening) in Germany after five years of follow-up. The addition of these new results to the all-cause mortality analysis did not significantly alter the results (RR 1.20, 95% CI 0.83-1.73).…”
mentioning
confidence: 99%